Developing a Causal Model of Academic Buoyancy in Gifted Students in Tehran Based on Perceived Parental Relationships and Perceived Teacher–Student Relationships: The Mediating Role of Academic Pressure and Socio-Emotional Competence - Ershadi Manesh, Soudabeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to develop and test a causal model of academic buoyancy in gifted secondary school students based on perceived parent–child relationships and teacher–student relationship quality, with the mediating roles of socio-emotional competence and perceived academic pressure.Methods and Materials: The study adopted an applied, descriptive–correlational design using structural equation modeling (SEM). The population consisted of gifted students enrolled in the first and second levels of secondary education in Tehran during the 2023–2024 academic year. A total of 392 students were selected through simple random sampling. Data were collected using standardized questionnaires assessing academic buoyancy, parent–child relationships, teacher–student relationship quality, socio-emotional competence, and perceived academic pressure. Data analysis was conducted using SPSS and AMOS software. Pearson correlation coefficients were calculated, and SEM with maximum likelihood estimation was employed. Indirect effects were tested using bootstrapping with 2,000 resamples to evaluate mediating pathways.Findings: Structural equation modeling indicated that mother–child relationships (β = 0.37, p < .05) and teacher–student relationship quality (β = 0.42, p < .05) had significant direct positive effects on academic buoyancy, whereas the direct effect of father–child relationships was not significant. Socio-emotional competence showed a strong positive direct effect on academic buoyancy (β = 0.45, p < .01), while perceived academic pressure had a significant negative direct effect (β = −0.39, p < .01). Bootstrapping results revealed significant indirect effects of parent–child relationships and teacher–student relationship quality on academic buoyancy through socio-emotional competence (positive) and perceived academic pressure (negative). The overall model demonstrated acceptable goodness-of-fit indices.Conclusion: The findings highlight academic buoyancy as a relationally embedded and psychologically mediated construct, indicating that supportive parental and teacher relationships enhance gifted students’ vitality primarily by strengthening socio-emotional competence and reducing perceived academic pressure.